Liberating economics : feminist perspectives on families, work, and globalization - Barker, Drucilla K., 1949- (Advances in heterodox economics., 2004)
The authors draw central concepts from women's studies scholarship to construct a feminist understanding of the economic roles of families, caring labour, motherhood, paid and unpaid labour, poverty, the feminization of labour and the consequences of globalization.